2020
DOI: 10.1007/s10874-020-09401-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wind speed on the level of particulate matter PM10 concentration in atmospheric air during winter season in vicinity of large combustion plant

Abstract: The concentrations of suspended particulate matter PM10 in two-month winter period, i.e. December–January in years 2009–2015, were analyzed in relation to the values of wind speed in that time. It was possible to analyze results of air pollution measurements performed in the measuring station from the perspective of their higher levels in winter seasons (so-called smog episodes). Results from 3 stations of the Regional Inspectorate for Environmental Protection in Poznań (WIOŚ Poznań) served for better presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…A study in Israel found a statistically significant relationship between wind direction of industrial areas and asthma prevalence (54). A recent study in Poland that looked at PM 10 concentrations in atmospheric air during winter was affected by wind speeds; the result was that there would be a higher increment of PM 10 particulate matter values when wind speeds were lower in the air (8). In addition to considering wind direction in mobilizing air pollution emission displacement from a region, it is also necessary to consider the wind speed, so that it can assess and predict whether air pollution emissions carried by the wind come from the same pollutant source and can estimate the distance the pollution will drop to the ground.…”
Section: Wind Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Israel found a statistically significant relationship between wind direction of industrial areas and asthma prevalence (54). A recent study in Poland that looked at PM 10 concentrations in atmospheric air during winter was affected by wind speeds; the result was that there would be a higher increment of PM 10 particulate matter values when wind speeds were lower in the air (8). In addition to considering wind direction in mobilizing air pollution emission displacement from a region, it is also necessary to consider the wind speed, so that it can assess and predict whether air pollution emissions carried by the wind come from the same pollutant source and can estimate the distance the pollution will drop to the ground.…”
Section: Wind Directionmentioning
confidence: 99%
“…Gas emissions such as sulphur trioxide (SO 3 ), carbon monoxide (CO), sulphur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), nitric oxide (NO x ), and carbon dioxide (CO 2 ) are the residue from burning coal with oxygen (5). Various health problems, both directly and indirectly, are related to these gases' emission (7)(8). Burning coal from power plants produces emissions of CO 2 , CO, NO x , and SO 2 gases that interact with particulate matter, change the ambient air quality to become polluted, leading to increased attacks of respiratory diseases (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Meteorology that has a big influence on changes in pollutant concentrations is wind speed. Pollution spread in an area is inseparable from the influence of strong wind speeds (Cichowicz et al, 2020). In addition to wind speed, mixing height also affects the dispersion of pollutants.…”
Section: Weather Descriptionmentioning
confidence: 99%
“…High concentrations of pollutants generated by human activity occur especially in industrial areas and cities, as well as in other spaces such as agricultural or recreational areas. These pollutants directly and indirectly affect the air quality not only around the source of the pollution, but also in the surrounding area [2][3][4][5][6][7]. The main pollutants according to criteria established for the protection of human health and plant protection are particulate matter (PM10, PM2.5, and increasingly PM1.0) and gaseous pollutants such as benzene, nitrogen dioxide, sulfur dioxide, carbon monoxide, ozone, lead, arsenic, cadmium, nickel, and benzo (a) pyrene in PM10 dust, as well as hydrogen sulfide (H 2 S) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%